Fenomena Gaya Hidup Gen Z Indonesia (Antara Tren Perilaku Impulsive dan Rekognisi Positive Emotion) - Bambang Mudjiyanto; Launa; Hafzotillah; Priatna Kusuma; Nursyamsi (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This study seeks to examine the behavior of Gen Z from an alternative point of view, that Gen Z also has positive life attitudes and behaviors, which cannot be labeled as impulsive and panic. Through qualitative analysis with a phenomenological approach and virtual ethnography, this study concludes that as an entity that grew up under the influence of virtual ecology and digital ecosystem, theoretically Gen Z has unique attitudes and behaviors, namely social awareness, political views, and alignment with sensitive public issues, not just impulsive, panic, hedon, and consumptive. Understanding Gen Z's perspective, challenges, and optional ideas-sometimes critical-idealistic, but sometimes taking quick and practical solutions-will help us understand Gen Z's psychographic dynamics more fully and proportionally. Delving into the unique, varied and dynamic character of Gen Z is an important asset for all parties who want to connect and benefit from this entity, because Gen Z, in the future, will be a potential entity that can determine the black and white face of the nation's economy, politics, social and culture.